Deficiency of Isoprenylcysteine Carboxyl Methyltransferase (ICMT) Leads to Progressive Loss of Photoreceptor Function - Christiansen, Jeffrey R. (J Neurosci, 2016)
Retinal neurons use multiple strategies to fine-tune visual signal transduction, including post-translational modifications of proteins, such as addition of an isoprenyl lipid to a carboxyl-terminal cysteine in proteins that terminate with a “CAAX motif.” We previously showed that RAS converting enzyme 1 (RCE1)-mediated processing of isoprenylated proteins is required for photoreceptor maintenance and function. However, it is not yet known whether the requirement for the RCE1-mediated protein processing is related to the absence of the endoproteolytic processing step, the absence of the subsequent methylation step by isoprenylcysteine methyltransferase (ICMT), or both. To approach this issue and to understand the significance of protein methylation, we generated mice lacking Icmt expression in the retina. In the absence of Icmt expression, rod and cone light-mediated responses diminished progressively. Lack of ICMT-mediated methylation led to defective association of isoprenylated transducin and cone phosphodiesterase 6 (PDE6α′) with photoreceptor membranes and resulted in decreased levels of transducin, PDE6α′, and cone G-protein coupled receptor kinase-1 (GRK1). In contrast to our earlier findings with retina-specific Rce1 knock-out mice, rod PDE6 in Icmt-deficient mice trafficked normally to the photoreceptor outer segment, suggesting that the failure to remove the −AAX is responsible for blocking the movement of PDE6 to the outer segment. Our findings demonstrate that carboxyl methylation of isoprenylated proteins is crucial for maintenance of photoreceptor function. SIGNIFICANCE STATEMENT In this report, we show that an absence of isoprenylcysteine methyltransferase-mediated protein methylation leads to progressive loss of vision. Photoreceptors also degenerate, although at a slower pace than the rate of visual loss. The reduction in photoresponses is due to defective association of crucial players in phototransduction cascade. Unlike the situation with RCE1 deficiency, where both methylation and removal of −AAX were affected, the transport of isoprenylated proteins in isoprenylcysteine methyltransferase-deficient retinas was not dependent on methylation. This finding implies that the retention of the −AAX in PDE6 catalytic subunits in Rce1(−/−) mice is responsible for impeding their transport to the rod photoreceptor outer segment. In conclusion, lack of methylation of isoprenylcysteines leads to age-dependent photoreceptor dysfunction.